Reviews of recent publications (Studies in 20th & 21st Century Literature, 1998)
Johnson, Roberta. Crossfire: Philosophy and the Novel in Spain 1900-1934 by Nina L. Molinaro Lucey, Michael. Gide 's Bent: Sexuality, Politics, Writing by Jocelyn Van Tuyl Morris, Alan. Patrick Modiano by David Herman Sartiliot, Claudette. Citation and Modernity: Derrida, Joyce, and Brecht by Siegfried Mews
Keywords: Roberta Johnson; Crossfire: Philosophy and the Novel in Spain 1900-1934; Nina L. Molinaro; Michael Lucey; Gide' s Bent: Sexuality Politics Writing; Jocelyn Van Tuyl; Alan Morris; Patrick Modiano; David Herman; Claudette Sartiliot; Citation and Modernity: Derrida Joyce and Brecht; Siegfried Mews